Оцінювання результативності оперативного менеджменту зовнішньоекономічної діяльності підприємства - Гришко, Н.В.; Любич, Б.Б. (Економіка промисловості, 2013)
Досліджено підходи до формування системи показників результативності управління. Запропоновано метод комплексного оцінювання результативності оперативного управління зовнішньоекономічною діяльністю, що ґрунтується на програмно-цільовому підході та синергізмі в управлінні. Исследованы подходы к формированию системы показателей результативности управления. Предложен метод комплексного оценивания результативности оперативного управления внешнеэкономической деятельностью, который основан на программно-целевом подходе и синергизме в управлении.
Ключевые слова: внешнеэкономическая деятельность, менеджмент, оценка, предприятие, программно-целевой подход, результативность, синергизм. The one of the most important problems for enterprises is to build productive and effective system of management. It will provide quick reaction and effective response to competition changes in international markets. Therefore, capacity and outputs comparison system, enterprise operational management effectiveness evaluation and diagnostic are urgent issues in circumstances of competitive pressure.
The goals of the research are to choose an actual criterion of enterprise foreign-economic management effectiveness and to form an integrated approach to the operational management evaluation based on managerial specifics. Different approaches to the enterprise effectiveness rates systematization were investigated. The method of the operational management evaluation based on program-target approach and the fussy logic using was offered. The estimation of management system rank was conducted with synergistic result of several elements interaction measurement. As a result of the research an integrated index was offered. Its advantages are using simplicity, fast reaction to enterprise state changes and taking note of contributory managerial specifics under the competitive environment pressure.
Keywords: foreign-economic activity, management, evaluation, enterprise, program-target approach, effectiveness, synergy.